Impact of different cooking methods on the chemical profile of high-oleic acid peanut seeds. (15th June 2022) - Xiao, Yuan; Liu, Hao; Du, Puxuan; Liang, Xuanqiang; Li, Haifen; Lu, Qing; Li, Shaoxiong; Liu, Haiyan; Hong, Yanbin; Varshney, Rajeev K.; Chen, Xiaoping
Highlights: 630 metabolites were identified in processed high oleic acid (OA) peanut seeds. Bioactive substances were maximally preserved in baked high-OA peanuts. Frying is not suit for cooking peanut, which down-regulated 207 metabolites. Cross-validation analysis suggests that widely targeted metabolomics is reliable. Abstract: High oleic acid (OA) peanut seeds (PS) can be beneficial for human health. However, chemical variations in high-OA PS after domestic cooking are not fully understood. In order to investigate the impact of different cooking methods on the chemical profile of high-OA PS, widely established metabolomics approach was employed to identify the relative contents of PS metabolites. Herein, 630 metabolites within 27 categories were characterized in PS, of which 141, 157, 402 differential metabolites were observed in each treatment group (boiling, baking, and frying) when compared to the raw seed. Accordingly, bioactive substances were maximally preserved in baked high-OA PS. Further conventional methods (HPLC-UV/GC–MS) quantified the absolute composition of amino and fatty acids, verifying the reliability of metabolomic analysis. Collectively, the understanding of the phytochemical substances in relation to the domestic cooking method established a foundation for future high-OA PS processing.